Factors affecting outcome in children with snake envenomation: a prospective observational study. Issue 8 (28th May 2013) - Sankar, Jhuma; Nabeel, Rehana; Sankar, M Jeeva; Priyambada, Leena; Mahadevan, S
Abstract : Objectives: To evaluate clinical outcome and factors affecting outcome in children with snake envenomation. Design: Prospective observational study. Setting: Paediatric intensive care unit of a tertiary care teaching hospital in India. Patients: We prospectively enrolled children ≤12 years of age admitted to our hospital with a definitive history of snake bite from August 2007 to June 2010. Measurements and Main Results: Demographic characteristics and clinical course of the enrolled children were recorded in a structured proforma and analysed using appropriate statistical methods. Children were treated as per the WHO guidelines (2005) on the management of snake bite in children. Of 110 children studied, 77 (69%) were male. Most (72; 64.2%) had features predominantly of haematotoxic envenomation while 20 (18%) and 18 (16%) children had features of neurotoxic envenomation and local involvement, respectively. 14 children (13%) died and 13 (12%) had major disabilities. On univariable analysis, the following prehospital and admission variables were found to be significantly associated with poor outcome: age, walking for >1 km after the bite, vomiting, haemoglobin ≤10 g/dl at admission and species of snake (cobra). On multivariable analysis, only younger age (adjusted OR 0.85; 95% CI 0.7 to 0.9), walking for >1 km after the bite (adjusted OR 57; 95% CI 4.2 to 782) and haemoglobin ≤10 g/dl at admission (adjusted OR 6; 95% CI 2 to 18.2) remained significant. Conclusions: Younger age at presentation, anaemia (haemoglobin ≤10 g/dl) and distance walked after the bite may be independent predictors of mortality and morbidity in children with snake bite. These features in victims of snake bite warrant early referral to and management in tertiary care centres.